What if mathematics is learned using ODL in Hogwarts? / Siti Nurleena Abu Mansor, Mahanim Omar and Siti Mariam Saad - Abu Mansor, Siti Nurleena; Omar, Mahanim; Saad, Siti Mariam (Unit Penerbitan JSKM, 2020)
Mathematics is always great and fun as pictured in Hidden Figure movie, with excellent understanding the applications are enormous. It even gave impacts on space travel and its role crafted in modern history. However, when the theories and concepts are misunderstood, it changed to Nightmare on the Elm Street. Leading the students to take it or leave it. In learning mathematics, teacher plays an important role to deliver the content in the most understandable and creative ways of teaching to gasp the students' attention (Preciado- Babb, Metz, Sabbaghan, & Davis, 2018). Many methods of teaching have been implemented that suited the teachers' and students' preferences (Sankar & Karri, 2016; Khoshaim & Subhi- Aiad, 2018). Even in the current situation of Covid-19 pandemic that lead to Movement Control Order (MCO) by the government, the learning must continue. Students stay safe at home, and teachers continue to deliver the courses. One of the methods used is Online and Distance Learning (ODL) using learning management system (LMS). From the views of us as mathematics teachers, here are some tips for the teachers and the students in learning mathematics through ODL. In order to make it interesting, we used Harry Potter movie as the narrative of the situation and tips in commencing ODL with the students.